PENERAPAN PEMBELAJARAN SAINTIFIK SEBAGAI ALTERNATIF MENINGKATKAN HASIL BELAJAR DAN KETRAMPILAN SISWA - Siswati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2023)
The learning demands of the 21st century and the independent learning curriculum are innovative and student-based learning. Scientific learning is one of the real innovative learning, one of which is done through science learning. The aims of this study were: (1) Applying scientific learning to science subjects (2) Providing students with knowledge and skills about real learning. This type of research is descriptive through a qualitative approach. Collecting learning knowledge data through objective tests while for learning skills data through questionnaires. The subjects of this study were students of grade 7 in science subjects. The results of the study showed: (1) 87% of students' responses to scientific learning strongly agreed; (2) learning outcomes through scientific learning increased from the mean pre-test (67.4) and post-test (83.6); and from the results of the skills questionnaire obtained an average value of 85.6.